Diarrhea in the HIV-Infected Patient - Peter Phillips (Canadian Journal of Infectious Diseases)
Gastrointestinal manifeslations may be encountered throughout, the course of HIV disease. The problems range from asymptomatic hairy leukoplakia lo overwhelming diarrhea due to opportunistic infections such as cryptosporidiosis. Diarrheal disease is an important contributing factor to wasting in advanced HIV disease. Considerable progress has been made in recents years regarding our understanding or HIV-related diarrhea, including etiological agents, diagnostic methods and treatment.